TRADE-INS STRATEGY FOR A DURABLE GOODS FIRM FACING STRATEGIC CONSUMERS - Chen, Jen-Ming (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
Trade-ins rebate from the manufacturer to the consumers is a commonly used device by a durable goods firm to price discriminate between new and replacement buyers. it creates segment effect by offering different prices to different groups of customers. This study deals with such an effect by considering three trade-ins policies facing the firm, i.e., no trade-ins, trade-ins to replacement consumers with high quality used goods, and trade-ins to all replacement consumers. This studfy determines the optimal pricing and/or trade-ins rebate, and examines the strategic choice among the three options facing the firm. We develop analytic models that incorporate key features of durable goods into model formulation, namely the deterioration rate and the quality variation of the used goods. Our research findings include: the strategic choice among the three options depends critically on the two features and the price of new goods, and the trade-ins-to-all policy outperforms the others when the deterioration rate is high and/or new goods price is high.